Congenital cervicofacial cysts and fistulas associated with the first branchial sulcus - Farcic, Antonio; Bounous, Mario; Gardiol, Valdo; De Los Santos, Julio (Cirugía del Uruguay, 1977)
Existing case material on lateral congenital cysts and fistulas in the neck is enlarged by two cases, successfully treated by the authors, in the first surgical-attempt: a cyst located in the parotid lodge and a preauricular fistula. Their connection with the first branchial cleft is discussed, together with their pathological and clínical characteristics, complementary tests of assistance for the purpose of correct diagnosis, and guidelines for the surgical tactics and technique required if recurrence is to be avoided.